Answer: Your right!
-8n-13
Step-by-step explanation:
-2(4n-1)+15=
-8n+2-15
Combine like terms- 2-5= -13
so -8n-13
Answer:
in my ipinion...
Step-by-step explanation:
let a no.be x
1/3*x+77=33
1/3*x=-44
x=-44*3
x=-132
The <span>expression that represents n plus 7 multiplied by 3 is
(n + 7)(3)
The entire expression, (n + 7) is multiplied by 3 since it would be inconvenient to state the expression as given above if what is meant was
(n + 7x3). It would have simply been n plus 21.</span>
B I have done this before
Answer:
3rd Answer =Option A is the Correct Answer
Step-by-step explanation: